Manajemen Risiko Keselamatan Dan Kesehatan Kerja Dengan Metode Hazard Identification Risk Assessment And Risk Control (HIRARC)Dalam Upaya Mencapai Zero Accident (Studi Kasus: Part Manufactur Division (PMD) PT. Omron Manufacturing of Indonesia) - Wibowo, Dwi Ari, Ir. Muchlison Anis, MT (2016)
Every work environment regardless of the danger. Various technologies and equipment in addition to beneficial life also bring harm to use. As problems in the division PMD (Part Manufacture Division) PT. OMI still be accidents. Management of Health and Safety conducted using Hazard Identification Risk Assessment and Risk Control (HIRARC) to achieve zero accident the company. HIRARC is a document that contains the hazard identification, risk assessment and control of risks in order to reduce the occurrence of occupational safety and health disorders. Hazard risks that threaten the health and safety hazards such as electrical machinery, physical, and chemical material. Percentage risk assessment PMD division at negligible levels of 0%, low risk 10%, moderate risk 22%, high risk 37%, and extreme 31%. Control is applied as engineering controls , administrative, and personal protective equipment for operators.